PERBEDAAN HASIL BELAJAR MATA KULIAH KEAGAMAAN MAHASISWA PAI ANGKATAN 2019 BERDASARKAN LATAR BELAKANG PENDIDIKAN SLTA - Deni Irawati; Supriadi (CV. ADIBA ASIHA AMIRA, 2024)
The background of this research is that there are differences in the learning outcomes of 2019 PAI students in religious courses. Researchers see that there are differences in the learning outcomes of students with a religious education background in religious subjects which should be higher than students with a general education background. This research is a comparative quantitative research. sample of 42 students. The instrument that the researcher used was a test of 24 questions about religious subjects. can be seen from the learning outcomes of students with general education background, the test score with the highest score is 100 and the lowest score is 46. The total score is 1462.5 and the average is 81.25. it can be seen from the learning outcomes of students with religious education backgrounds, the test scores obtained with the highest score are 100 and the lowest score is 50. The total score is 1808 and the average is 75.34.